$a\vee b=b\vee a$

$a\wedge b=b\wedge a$

Kyle Sutton
2022-07-13
Answered

Proof of commutative property in Boolean algebra

$a\vee b=b\vee a$

$a\wedge b=b\wedge a$

$a\vee b=b\vee a$

$a\wedge b=b\wedge a$

You can still ask an expert for help

conveneau71

Answered 2022-07-14
Author has **17** answers

First we prove idempotency $a=a\vee a$, though we might not need it later on.

$a=a\vee 0=a\vee (a\wedge {a}^{\prime})=(a\vee a)\wedge (a\vee {a}^{\prime})=(a\vee a)\wedge 1=a\vee a$

Second, we prove uniqueness of the complement, in the sense that

$a\wedge b=0,\text{}b\vee a=1\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}b={a}^{\prime}$

${a}^{\prime}={a}^{\prime}\wedge 1={a}^{\prime}\wedge (b\vee a)=({a}^{\prime}\wedge b)\vee ({a}^{\prime}\wedge a)={a}^{\prime}\wedge b\phantom{\rule{0ex}{0ex}}b=1\wedge b=(a\vee {a}^{\prime})\wedge b=(a\wedge b)\vee ({a}^{\prime}\wedge b)={a}^{\prime}\wedge b$

In particular, it implies ${a}^{\u2033}=a$.

Then certain forms of absorbance follows: $a=a\vee (b\wedge a)$

${a}^{\prime}\vee (a\vee (b\wedge a))=1\phantom{\rule{0ex}{0ex}}(a\vee (b\wedge a))\wedge {a}^{\prime}=(a\wedge {a}^{\prime})\vee (b\wedge a\wedge {a}^{\prime})=0$

We similarly get $a=(a\wedge b)\vee a$, and two other equations by duality.

Then, we get a key lemma: $a\vee b=1\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}{a}^{\prime}={a}^{\prime}\wedge b\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}b\vee a=1$:

Supposed $a\vee b=1$, we get ${a}^{\prime}={a}^{\prime}\wedge 1={a}^{\prime}\wedge (a\vee b)=({a}^{\prime}\wedge a)\vee ({a}^{\prime}\wedge b)={a}^{\prime}\wedge b$.

Supposed ${a}^{\prime}={a}^{\prime}\wedge b$, we get $b\vee {a}^{\prime}=b\vee ({a}^{\prime}\wedge b)=b$ by absorbance, so

$\text{}b\vee a=(b\vee {a}^{\prime})\vee a=1$

Note that this implies $a\vee x\vee {a}^{\prime}=1$ for any $x$, as we have $\text{}(x\vee {a}^{\prime})\vee a=1$.

Using their dual statements as well ($a\wedge b=0\phantom{\rule{thickmathspace}{0ex}}\u27fa\phantom{\rule{thickmathspace}{0ex}}b\wedge a=0$ and ${a}^{\prime}\wedge x\wedge a=0$), we can finally arrive to commutativity by observing that both $a\vee b$ and $b\vee a$ are complements of ${a}^{\prime}\wedge {b}^{\prime}$:

$(a\vee b)\vee ({a}^{\prime}\wedge {b}^{\prime})=(a\vee b\vee {a}^{\prime})\wedge (a\vee b\vee {b}^{\prime})=1\phantom{\rule{0ex}{0ex}}(b\vee a)\vee ({a}^{\prime}\wedge {b}^{\prime})=(b\vee a\vee {a}^{\prime})\wedge (b\vee a\vee {b}^{\prime})=1\phantom{\rule{0ex}{0ex}}-\cdot -\cdot -\phantom{\rule{0ex}{0ex}}({a}^{\prime}\wedge {b}^{\prime})\wedge (a\vee b)=({a}^{\prime}\wedge {b}^{\prime}\wedge a)\vee ({a}^{\prime}\wedge {b}^{\prime}\wedge b)=0\phantom{\rule{0ex}{0ex}}({a}^{\prime}\wedge {b}^{\prime})\wedge (b\vee a)=({a}^{\prime}\wedge {b}^{\prime}\wedge b)\vee ({a}^{\prime}\wedge {b}^{\prime}\wedge a)=0$

$a=a\vee 0=a\vee (a\wedge {a}^{\prime})=(a\vee a)\wedge (a\vee {a}^{\prime})=(a\vee a)\wedge 1=a\vee a$

Second, we prove uniqueness of the complement, in the sense that

$a\wedge b=0,\text{}b\vee a=1\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}b={a}^{\prime}$

${a}^{\prime}={a}^{\prime}\wedge 1={a}^{\prime}\wedge (b\vee a)=({a}^{\prime}\wedge b)\vee ({a}^{\prime}\wedge a)={a}^{\prime}\wedge b\phantom{\rule{0ex}{0ex}}b=1\wedge b=(a\vee {a}^{\prime})\wedge b=(a\wedge b)\vee ({a}^{\prime}\wedge b)={a}^{\prime}\wedge b$

In particular, it implies ${a}^{\u2033}=a$.

Then certain forms of absorbance follows: $a=a\vee (b\wedge a)$

${a}^{\prime}\vee (a\vee (b\wedge a))=1\phantom{\rule{0ex}{0ex}}(a\vee (b\wedge a))\wedge {a}^{\prime}=(a\wedge {a}^{\prime})\vee (b\wedge a\wedge {a}^{\prime})=0$

We similarly get $a=(a\wedge b)\vee a$, and two other equations by duality.

Then, we get a key lemma: $a\vee b=1\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}{a}^{\prime}={a}^{\prime}\wedge b\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}b\vee a=1$:

Supposed $a\vee b=1$, we get ${a}^{\prime}={a}^{\prime}\wedge 1={a}^{\prime}\wedge (a\vee b)=({a}^{\prime}\wedge a)\vee ({a}^{\prime}\wedge b)={a}^{\prime}\wedge b$.

Supposed ${a}^{\prime}={a}^{\prime}\wedge b$, we get $b\vee {a}^{\prime}=b\vee ({a}^{\prime}\wedge b)=b$ by absorbance, so

$\text{}b\vee a=(b\vee {a}^{\prime})\vee a=1$

Note that this implies $a\vee x\vee {a}^{\prime}=1$ for any $x$, as we have $\text{}(x\vee {a}^{\prime})\vee a=1$.

Using their dual statements as well ($a\wedge b=0\phantom{\rule{thickmathspace}{0ex}}\u27fa\phantom{\rule{thickmathspace}{0ex}}b\wedge a=0$ and ${a}^{\prime}\wedge x\wedge a=0$), we can finally arrive to commutativity by observing that both $a\vee b$ and $b\vee a$ are complements of ${a}^{\prime}\wedge {b}^{\prime}$:

$(a\vee b)\vee ({a}^{\prime}\wedge {b}^{\prime})=(a\vee b\vee {a}^{\prime})\wedge (a\vee b\vee {b}^{\prime})=1\phantom{\rule{0ex}{0ex}}(b\vee a)\vee ({a}^{\prime}\wedge {b}^{\prime})=(b\vee a\vee {a}^{\prime})\wedge (b\vee a\vee {b}^{\prime})=1\phantom{\rule{0ex}{0ex}}-\cdot -\cdot -\phantom{\rule{0ex}{0ex}}({a}^{\prime}\wedge {b}^{\prime})\wedge (a\vee b)=({a}^{\prime}\wedge {b}^{\prime}\wedge a)\vee ({a}^{\prime}\wedge {b}^{\prime}\wedge b)=0\phantom{\rule{0ex}{0ex}}({a}^{\prime}\wedge {b}^{\prime})\wedge (b\vee a)=({a}^{\prime}\wedge {b}^{\prime}\wedge b)\vee ({a}^{\prime}\wedge {b}^{\prime}\wedge a)=0$

gaiaecologicaq2

Answered 2022-07-15
Author has **6** answers

Your proof of join-idempotency uses a form of distributivity that is not part of the axioms. Of course that one will follow from the ones we have and the absorption laws, which could be proven first. On the other hand, if I didn't miss anything, you didn't really use any idempotency law.

asked 2022-01-24

What are the standard three-dimensional unit vectors?

asked 2021-09-21

For the following exercises, enter the data from each table into a graphing calculator and graph the resulting scatter plots. Determine whether the data from the table would likely represent a function that is linear, exponential, or logarithmic. $\begin{array}{|ccccccccccc|}\hline x& 1& 2& 3& 4& 5& 6& 7& 8& 9& 10\\ f\left(x\right)& 3.05& 4.42& 6.4& 9.28& 13.46& 19.52& 28.3& 41.04& 59.5& 86.28\\ \hline\end{array}$

asked 2021-08-20

By using the transformation of function y=|x|, sketch the function of y=|x-3|+2

asked 2021-02-11

What is the slope of EF if E is (0,-2) and F is (3, 2.5)

asked 2021-06-25

Simplify ${x}^{2}-3x-4\xf7(x+2)$

asked 2021-03-06

Find the x-and y-intercepts of the graph of the equation algebraically.

$\frac{8x}{3}+50-2y=0$

asked 2022-01-13

Prove that:

Every$\mathbb{Q}$ - vector space $V\ne 0$ is not free over subring $\mathbb{Z}\subset \mathbb{Q}$

Every